Analisis Penggunaan Bahasa Campuran (Code-Mixing) Dalam Bisnis Pemasaran Berbasis Digital - Nurrahma, Avinta Ika; Damayanti, Ervina; Agustin, Rossi Rahma Nabilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the effectiveness of mixed language use in digital marketing businesses and to determine the positive and negative impacts of code-mixing. This research method uses an interdisciplinary approach to combine linguistic, economic, and social aspects. This method involves collecting data from various advertisements, posts, or even content from social media or e-commerce platforms that use mixed language and analyzing its usage patterns. Furthermore, data collection was conducted through interviews with young entrepreneurs who market their products online. The results of this study indicate that English plays a more important role as a lingua franca, a necessary language for influence in business and marketing. English is most commonly used in online marketing. The use of code-mixing is also frequently found in product marketing advertisements. Meanwhile, correct or standard English is not essential for business and marketing purposes. Most studies indicate that code-mixing has a significant impact on business and marketing. Based on the results of these interviews, it can be concluded that the use of mixed language has a positive impact on increasing potential consumer interest and purchasing decisions. Meanwhile, the negative impact is audience misunderstanding due to the use of unfamiliar vocabulary.